Mechanochemical synthesis and dehydrogenation properties of Yb(AlH4)3. (29th July 2021) - Cao, Zhijie; Felderhoff, Michael
Abstract: The facile synthesis of ytterbium tetrahydroaluminate Yb(AlH4 )3 is conducted by a mechanochemical procedure under hydrogen atmosphere for the first time. Results show that the synthesized Yb(AlH4 )3 remains as an amorphous state. The thermal decomposition of Yb(AlH4 )3 goes through a four-stage pathway with several amorphous intermediate phases during the process. The first dehydrogenation step of Yb(AlH4 )3 presents a relatively low apparent activation energy of 99.6 kJ mol −1, and ninety percent of the hydrogen from this stage can be liberated within 20 min at 160 ° C. Rehydrogenation tests above 160 ° C and 14 MPa hydrogen pressure demonstrate the unsuccessful rehydrogenations of the first decomposition step due to the formation of a thermodynamically more stable compound YbHCl. Highlights: A novel transition metal alanate Yb(AlH4 )3 is prepared. A solvent-free mechanochemical procedure is developed. Yb(AlH4 )3 remains as an amorphous state. The thermal decomposition goes through a four-stage pathway. The first dehydrogenation step presents a low apparent activation energy.